Hyperons and massive neutron stars: vector repulsion and strangeness - Weißenborn-Bresch, Simon Alexander; Chatterjee, Debarati; Schaffner-Bielich, Jürgen (Nuclear physics. A, Nuclear and hadronic physics, 2013)
Finding the composition of cold dense matter is still a serious challenge. Recent neutron star observations, especially the observed mass of pulsar PSR J1614-2230 with M=(1.97±0.04)M⊙, constrain the equation of state (EoS) of hadronic matter and question the existence of hyperons in the core of neutron stars. As in previous work, we investigate the conditions for the presence of hyperons in the neutron star core by exploring the vector baryon-meson coupling assuming flavor SU(3) symmetry. However, as an extension to our work, we investigate the full range of SU(3) parameters which had previously been kept fixed.